Fibroblast contributes to osteoblast differentiation in a sonic hedgehog signaling-independent manner - Fernandes, Célio Junior da Costa [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
We hypothesized that communication between osteoblast and fibroblasts (FB) contributes to bone dynamic tissue. We harvested cell-free supernatants from fibroblast to treat osteoblast for testing viability and differentiation mechanisms, mainly monitoring the involvement of Shh signaling in this paracrine mechanism. By exploring immunoblotting approach we have shown that FB-released factors interfere on osteoblast metabolism by up-regulating the phosphorylation of FAK and Rac-1 proteins at the early stage and later contributing with osteoblast differentiation by upmodulating alkaline phosphatase (ALP) and in vitro mineralization. During osteoblast differentiation process, we also showed that Shh signaling proteins weren't upmodulated in disagreement with the osteogenic medium (O.M.) response, where Shh, Patched and Gli-1 were up-regulated. Altogether, our results show for the first time a possible mechanism involved on the crosstalk between fibroblast and osteoblast, since it is possible to observe that factors released from fibroblasts interfere on osteoblast metabolism at a Shh-independent manner. In this sense, we believe these results help us to understand the importance of the paracrine metabolism through bone resident cells for supporting bone dynamic biology, opening new avenues for comprehending bone diseases etiologies, as the case of osteoporosis

Não disponível
Keywords: Ossos; Proteínas; Fibroblastos; Hedgehog proteins